Chronic Kidney Disease in Hospital Cooks - Rita Ingewaty Wijaya; Dewi Sumaryani Soemarko (eJournal Kedokteran Indonesia, 2022)
Chronic kidney disease is still a concern for health problems in Indonesia. Complications of chronic kidney disease include hypertension, cardiovascular disease, decreased kidney function to the end stage and even death. One of the potential dangers is heat, which not only causes the risk of kidney and cardiovascular health problems but it can also worsen the condition of the disease. Workplaces such as hospital kitchens have a risk of heat exposure. This shows the importance of fit-to-work assessment based on occupational medicine management. A 55-year-old cook worker with stage IV chronic kidney disease came to the hospital. The result from the last visit suggested that she had dyslipidemia and uncontrolled hypertension. We recommend the worker with job restrictions. She can still work in the nutrition department of the hospital but with restrictions on cooking duties. She can still work in the food filter and serving area. The goal of limiting work assignments is to maintain chronic kidney failure at stage IV. In addition, the hospital is also required to take control measures so that other workers do not have the risk of kidney disease health problems. Keywords: chronic kidney disease, cook, occupational medicine management